Digital Leadership Strategies of School Principals in Addressing Educational Technology Disruption - Arman Paramansyah (Oikonomia : Journal of Management Economics and Accounting, 2026)
The rapid advancement of educational technology has created significant disruption in teaching, learning, and school management, requiring effective digital leadership from school principals. This study aims to analyze how digital leadership strategies of school principals can address technological disruption and enhance school transformation. The research employs a qualitative approach with a descriptive-analytical design using a literature-based method. Data were collected from reputable scholarly journal articles and analyzed through content and thematic analysis to identify key patterns related to digital leadership, organizational readiness, and technology integration. The findings reveal that digital leadership plays a crucial role in shaping school vision, strengthening teacher competencies, fostering digital culture, and supporting data-driven decision-making. Principals who adopt transformational and strategic leadership approaches are more effective in integrating technology into pedagogical practices and improving institutional performance. However, challenges such as limited infrastructure, low digital literacy, resistance to change, and ethical concerns remain significant barriers. The discussion highlights that successful digital transformation requires adaptive leadership, continuous professional development, strong governance, and ethical frameworks. In conclusion, digital leadership of school principals is a key determinant of school success in facing technological disruption when supported by organizational readiness and sustainable strategies.